Emulsifier-Free Water-in-Biodiesel Emulsion Fuel via Steam Emulsification: Its Physical Properties, Combustion Performance, and Exhaust Emission - Dhani Avianto Sugeng; Ahmad Muhsin Ithnin; Wira Jazair Yahya; Hasannuddin Abd Kadir (Energies, 2020)
The focus of this work is to investigate the effect of emulsifier-free emulsion fuel via steam emulsification (SD) to the diesel engine through physical properties, combustion performance, and exhaust analysis, and compare with conventional emulsion fuel with water percentages of 5% and 10% (E5 and E10) and biodiesel blend (B5). The SD was prepared using a custom 200 mL glass mixing column. The B5 fuel quantitatively was filled in the column, and then the steam was injected from the bottom of the mixing column through the porous frit glass with the pores ranging from 40 to 100 µm. The average water droplet size of SD is 0.375 µm with the average water percentage of 6.18%. The brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) of SD improved 4.19% and 3.92%, respectively, as compared to B5. The in-cylinder pressure (ICP) was lower than B5, however, yielding close to the B5 at 4 kW engine load. As for the exhaust emission test, NOx and PM for SD were reduced significantly with a percentage reduction of 25.22% and 10.68%, respectively, as compared to neat B5. The steam emulsification method offers a huge potential to be explored further as the concept offers the alternative method of making emulsion fuel without the use of conventional mechanical mixers.